Children’s digital skills acquisition in non-formal educational contexts: Pedagogical practices, learning, and inclusion opportunities in coding and robotics workshops - Cino, Davide; Brandsen, Silke; Bressa, Nathalie; Eriksson, Eva; Mascheroni, Giovanna; Zaman, Bieke (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2023)
Coding and robotics education has drawn a lot of interest in recent years to get children ready for the future labour market and advance their digital skills. This paper focuses on coding and robotics workshops in non-formal educational settings in Belgium, Denmark, and Italy. Building on data from a comparative/cross-national study, we will present findings from 16 observations of such workshops followed by 11 interviews with the organisers and moderators with the purpose of investigating their pedagogical practices, learning and inclusion opportunities. Findings of this study suggest that while digital skills workshops in non-formal learning contexts are designed and implemented with the goal of encouraging children's collaboration and active participation, the structure of the learning activities, the organization of the learning environment, and the choices made by children themselves may promote individualistic practices. Furthermore, despite attempts to encourage diversity and inclusion, such as choosing a "free" and "open-door" approach, these workshops may fail to attract participants from diverse backgrounds. We argue that an active dialogue between organisers and moderators, researchers, parents, and, of course, children from various backgrounds is required to promote child-centered approaches that move beyond individualistic accounts of learning and toward the creation of more collaborative and inclusive digital skill activities through a systemic and holistic approach.